A survey of the weevils of Ukraine. Bark and ambrosia beetles (Coleoptera: Curculionidae: Platypodinae and Scolytinae) - Nikulina, Tatyana; Mandelshtam, Mikhail; Petrov, Alexander; Nazarenko, Vitalij; Yunakov, Nikolai (Zootaxa, 2015)
Our knowledge of Ukrainian bark and ambrosia beetles (Coleoptera: Curculionidae: Scolytinae and Platypodinae) is summarized as a baseline for future studies of the fauna, with a checklist including information on distribution, host trees, biology and taxonomy. One hundred twenty-two species are recorded from Ukraine, of which seven are recorded for the first time. One species is recorded for the first time from Europe. Previous records of 24 species are considered dubious and requiring confirmation. In contrast to the Palaearctic Catalogue (Knížek 2011b), we consider Anisandrus maiche to be first described by Kurentsov (1941) rather than by Eggers (1942); A. maiche (Eggers, 1942) is a junior synonym of A. maiche (Kurentsov, 1941).